THE SEASONAL EFFECT ON THE BODY CONDITION OF DAIRY COWS IN EASTERN ALGERIA (Sciences & Technologie. C, Biotechnologies, 2016)
The aim of this study is to evaluate the body condition of dairy cows at different stages of lactation and analysis of the effect of the seasons on the body condition. From 2011 to 2015, we realized 1210 scoring on 564 lactations of 656 dairy cows. The average values are low; they are between 2.1 ± 0.4 to 2.7 ± 0.4 in the dry and calving periods and 1.2 ± 0.4 to 1.4 ± 0.4 in early lactation and 1.7 ± 0.5 to 2.2 ± 0.5 in mid-lactation. The differences in body condition scoring between seasons spring-summer and fall-winter are highly significant (P